Physical Fitness of Nigerian Armed Forces Personnel in their Flexibility in Federal Capital Territory Abuja - Suleiman, U. O.; Tsauri, Y. M.; Gwani, J. A.; Dikki, C. E.; Suleiman, M. A.; Achikasim, N. C.M. (NIU Journal of Social Sciences, 2018)
Physical fitness is of particular importance to Armed forces, not only because of its benefits, but also because it makes them battle ready. The main purpose of this study was to compare the physical fitness of Nigerian Army, Navy and Airforce personnel. To achieve this purpose, a sample of 235 subjects with mean age 31+ 5.4, years mean height 1.7 + 0.59, meters mean weight 63.2 + 74 were selected from the Nigerian Armed forces resident in Mogadishu Cantonment, Asokoro, Abuja. The sample comprised 80 Nigerian Army, 85 Navy and 70 Air force. sit and reach for flexibility was conducted to assess the subjects physical fitness. The data collected were analyzed to assess flexibility levels of Nigerian Army, Navy and Airforce personnel. The findings of this study revealed that the Nigerian Army personnel were better in flexibility (M=23.189Â±5.176) for sit and reach, than the Nigerian Navy and Airforce personnel. It was thus recommended that the physical fitness programme of the Nigerian Armed forces should be strengthened by increasing the frequency, intensity and duration of exercise to improve flexibility. Similarly, the Nigerian Armed forces should develop norms for different components of physical fitness for different age groups of different discipline, so as to improve their overall fitness and wellbeing.